Pembelajaran Peta Pikir (Mind Mapping) di Taman Baca OKL Street Library Desa Railor Kecamatan Malaka Tengah Kabupaten Malaka - Blegur, Willem Amu; Tey Seran, Krisantus Jumarto; Lestari, Anastasia Kadek Dety; Nahak, Agustinus Yasvin (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Literacy is believed to contribute plenty of benefits to both students and community helping them understand problems more clearly. One way to develop literacy is through building up reading habit. The border community, residing the border of Indonesia and Timor Leste, badly needs the literacy development both conceptually and feasibly through some practical techniques. One of the methods offered here is Mind Mapping. Mind mapping method gave benefits for users effectively and efficiently when they had implemented it simultaneously. People could write and took main issues from materials studied and kept long term. This activity was targeted at the OKL Street Library community or users that comprised students and volunteers who actively interacted at the OKL Street Library reading Venue. The aim to be achieved, was the enhancement of students and volunteers’ knowledge and skills towards a concept or a learning material in a more creatively, innovatively and participatorily by utilizing the mind mapping method. Students were also given a couple of books to increase their literacy culture. Such activity was carried out with the coordination of OKL Street Library, in terms of problems identification, determining the problem focus and for the mind mapping practiced and also books sharing which was collectively implemented by the team-work. Every students, volunteers and OKL SL founder felt happy and got benetif of these activities included understanding mind mapping and created point of view about how to maintain home and class freshly. The students modified it to state daily habits to be successed in their hobbies in future. We were looking forward to having more such activities or other development activities specially for lower primary students at OKL SL to help them enhance literacy competence that could benefit the whole community.